2006
DOI: 10.1002/bip.20515
|View full text |Cite
|
Sign up to set email alerts
|

Conformational differences in protein disulfide linkages between normal hair and hair from subjects with trichothiodystrophy: A quantitative analysis by Raman microspectroscopy

Abstract: Raman spectra of normal hair shafts and hair shafts from patients exhibiting trichothiodystrophy (TTD) were obtained using line focus laser illumination. Because hair from TTD patients has a significant decrease in the content of the sulfur-containing amino acids in comparison to normal hair, the 550-500 cm(-1) disulfide stretching mode region of the Raman spectrum was examined in detail. A quantitative spectral analysis demonstrates significant increases in the two energetically less favored gauche-gauche-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 44 publications
1
43
0
Order By: Relevance
“…96,205 Polarization microscopy can demonstrate the tiger-tail pattern of TTD, 217,218 which corresponds to the diagnostic low-sulfur protein content of the hair. 219,220 Special immunohistochemical procedures can be combined, eg, to confirm filaggrin deficiency in IV, 202,221 or demonstrate absent or reduced expression of LEKTI that supports the diagnosis of NS. [222][223][224] To screen for TGase-1 deficiency in ARCI unfixed cryostat sections are used for the enzyme activity assay.…”
Section: Use Of Ultrastructural Analysesmentioning
confidence: 99%
“…96,205 Polarization microscopy can demonstrate the tiger-tail pattern of TTD, 217,218 which corresponds to the diagnostic low-sulfur protein content of the hair. 219,220 Special immunohistochemical procedures can be combined, eg, to confirm filaggrin deficiency in IV, 202,221 or demonstrate absent or reduced expression of LEKTI that supports the diagnosis of NS. [222][223][224] To screen for TGase-1 deficiency in ARCI unfixed cryostat sections are used for the enzyme activity assay.…”
Section: Use Of Ultrastructural Analysesmentioning
confidence: 99%
“…[7][8][9][10][11] The inherent distinct sensitivities of these two techniques to molecular vibrations provide complementary structure and chemistry information. IR spectroscopic imaging studies of hair cross sections have been reported with synchrotron 12 and micro attenuated total reflection infrared microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the SÀ ÀS intensity of the hair from subjects with trichothiodystrophy (Brittle hair that has a cystine content of less than 50% compared with that of normal hair 33 ) significantly decreased compared with that of normal hair. 28 Considering this, it would be interesting and worthwhile to further investigate the internal structure changes of black human hair from Japanese females in their seventies or eighties due to aging. …”
Section: Discussionmentioning
confidence: 99%
“…The direct characterization of keratin fibers has been performed using X-ray diffraction, 1,[7][8][9][10][11][12] solid state NMR, 8,13 Raman, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and Infrared spectroscopy. 14,16,17 Information about the amorphous region (the cuticle and matrix) of…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation